Demography and Localized Reservoirs of Diversity Underlie Global Divergence in the Giant Kelp Macrocystis pyrifera - E. C. Giles; A. Zaiko; H. G. Hampton; P. Saenz‐Agudelo; M. Scriver; D. Crossett; A. Sim; X. B. Zhang; T. Jedrecka; C. O. Blain; L. Rauhina‐August; C. E. Cornwall; et al. (Molecular Ecology, 2026)
Accurate assessments of genetic diversity are crucial for effective management of natural resources. Numerous evolutionary mechanisms and genetic constraints can shape lineage divergence, challenging our quantification of biodiversity. Here, using whole genome resequencing of globally distributed giant kelp, Macrocystis pyrifera (Order: Laminariales), we show clear separation of genetic groups across the Pacific based on 99 genotyped individuals and 799,160 SNPs. Additionally, divergence across 88 genotyped individuals (53 derived in silico and 35 newly sequenced) considering 5,466,408 SNPs is attributed to both historical demographic processes and differential selection. Between Central California and the South Pacific (Chile, Tasmania, New Zealand), high divergence has occurred with very weak levels of gene flow, with concurrent timing of divergence. In parts of the South Pacific, kelp exhibited nucleotide diversity comparable to Central Californian populations but showed stronger signals of directional selection and excesses of rare alleles, with fewer genes showing signs of negative selection and some carbon‐related genes under positive selection. In contrast, Central Californian kelp had an excess of genes with synonymous mutations and showed evidence of a recent population contraction, as indicated by linkage disequilibrium and Tajima's D . In all populations, genome‐wide background divergence was paired with narrow genomic intervals of high nucleotide diversity and high linkage disequilibrium, which predominantly contained pervasive repetitive sequences. These repetitive regions were larger and more often shared among genetic groups in the South Pacific. They also appear to harbour genes of unknown function and alleles at intermediate frequency, suggesting that giant kelp maintain reservoirs of diversity within linked repeats, and this phenomenon is more pronounced in South Pacific M. pyrifera . Overall, the discovery of differential selection and structural variation as key drivers of divergence points to underappreciated genomic mechanisms of adaptation in kelp. These results will be useful for informing efforts to enhance climate resilience by identifying the evolutionary potential underlying kelp forest adaptation in the future.

Gut microplastics of two non-native freshwater fish species, Geophagus altifrons and Cichla orinocensis, in Singapore reservoirs - Xue Shen Teo; Kean Sim Lai; Jeffrey T. B. Kwik; Maxine A. D. Mowe; Darren C. J. Yeo (Aquatic Ecology, 2026)

First in situ observations of the goblin shark Mitsukurina owstoni - Aaron B. Judah; Alan J. Jamieson; Sarah R. D. Bingo; Megan E. Cundy; David A. Ebert; Steven Auscavitch; Harold K. Carlson; Tiffany Nicole G. Cunanan; Hayley B. Sims; Meagan Putts (Journal of Fish Biology, 2026)
We report the first live in situ observations of the iconic goblin shark ( Mitsukurina owstoni ) on a seamount near Jarvis Island in 2019 and on the slope of the Tonga Trench in 2024. Past observations are restricted to specimens hauled to the surface, resulting in limited knowledge of this species' ecology. These observations extend its known geographic and depth range considerably, and extend the depth range of lamniform sharks by 108 m. To further clarify habitat preferences and assess conservation status, further sampling, particularly with remote video, is required.

Pan‐Arctic Peatlands Have Expanded During Recent Warming - J. Handley; R. E. Fewster; T. G. Sim; S. Hodson; B. Parker; K. Crichton; D. Charman; K. Anderson; M. Garneau; M. Väliranta; D. W. Beilman; G. T. Swindles; et al. (Global Change Biology, 2026)
The fate of carbon stored in Arctic peatlands remains uncertain because of the complex nature of the effects of climate change on permafrost and peatland carbon cycling. Expansion and/or shrinkage of Arctic peatlands under climate change also remain unknown due to lack of ground data and difficulties detecting changes in the extent of these ecosystems, meaning that land surface model predictions currently inadequately quantify Arctic terrestrial carbon storage changes. Pan‐Arctic shifts in peatland extent would profoundly change the fate of carbon in the terrestrial Arctic. Here, we tackle this knowledge gap by answering three main questions: (a) has lateral expansion occurred in Arctic peatlands as a response to recent warming? (b) if so, how fast has this occurred? (c) how does the response vary regionally? To answer these, we collected a dataset (12 peatland sites, 91 peat cores) combining peat cores collected across two latitudinal (north–south) transects: one in the European Arctic and one in the Canadian Arctic. In each region, we selected three peatland sites, with cores collected from transects spanning the peat‐edge to the peat‐centre. Our large‐scale dataset shows that peatlands have expanded, often rapidly, with some rates exceeding ~1 m per year since 1950 AD. This rapid expansion has occurred during a period of widespread Arctic warming and is still ongoing: two thirds (8/12) of our peatland sites evidence new peat formation after ~1990 AD based on age‐depth models constrained by 14 C and 210 Pb dating. Given that our sites comprise a broad range of Arctic conditions, we expect peatland expansion to be a pan‐Arctic phenomenon. Within specific regions, there are constraints on peat expansion including topographical limits, but we present the basis for future work to estimate pan‐Arctic peatland expansion, plus the associated carbon cycle implications under future climate change.

Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

Pelagic sharks target long‐lived, retentive anticyclonic eddies in the Northwest Atlantic Ocean - Camrin D. Braun; Peter Gaube; Alice Della Penna; Simon R. Thorrold; Laura H. McDonnell; G. Chris Fischer; Gonzalo Mucientes; Nuno Queiroz; Mahmood Shivji; David W. Sims; Gregory B. Skomal; Bradley Wetherbee; et al. (Limnology and Oceanography, 2025)
Open ocean ecosystems represent the largest habitat on Earth and are highly dynamic in time and space. Mesoscale eddies are a primary driver of this variability and serve a key structural role in ocean ecosystems. Eddies modulate marine biodiversity beyond their impacts on plankton, influencing many ecologically and commercially important predators that may preferentially occupy anticyclonic eddies. However, how animal‐eddy interactions scale across predator species and the mechanistic drivers of these relationships remain an area of active research. We integrated satellite tracking data for sharks with observations of mesoscale eddies to determine how four shark species interact with eddies in the Gulf Stream region. Based on over 24,000 tracking days, we found that blue, white, and shortfin mako sharks selected for the cores of anticyclones while the use of eddies by tiger sharks was less conspicuous. Some particularly large and long‐lived anticyclones were occupied by tagged sharks for multiple weeks suggesting that these eddies may serve as hotspots for pelagic predators.

Strategically timing land protection decisions to enhance biodiversity benefits - Paul R. Armsworth; Rachel E. Fovargue; Amanda A. Hyman; Gwenllian D. Iacona; Charles B. Sims; Hyun Seok Yoon (Conservation Biology, 2025)
Choices conservation organizations make when designing and implementing protected area strategies affect the timing of land protection. Well‐timed habitat protection will have a greater impact on biodiversity outcomes; yet, decisions affecting the timing of protection have received much less attention than other aspects of protected area design. We reviewed evidence on the timing of protected area establishment and on temporal variation in factors influencing the ecological effectiveness and cost‐effectiveness of establishing protected areas. Protected area coverage often increases in episodic bursts rather than at some uniform rate. Moreover, temporal variation in biodiversity indicators, habitat conversion threats, and the cost of protecting land suggests that the conservation benefit of protecting land at some times will be greater than that at others. Conservation organizations increase their flexibility to choose when they protect land by using flexibility‐creating mechanisms, such as loans, multiyear budgeting, and endowment management. Models and theory suggest how this can be done to have the largest positive impact for conservation by exploiting long‐ and short‐term variation in factors that affect the rate of biodiversity return on protected area investments.

Genetic mixing in conservation translocations increases diversity of a keystone threatened species, Bettongia lesueur - Heidi M. Nistelberger; Emily Roycroft; Anna J. Macdonald; Shelley McArthur; Lauren C. White; Patrick G. S. Grady; Jennifer Pierson; Colleen Sims; Saul Cowen; Katherine Moseby; Katherine Tuft; Craig Moritz; et al. (Molecular Ecology, 2025)
Translocation programmes are increasingly being informed by genetic data to monitor and enhance conservation outcomes for both natural and established populations. These data provide a window into contemporary patterns of genetic diversity, structure and relatedness that can guide managers in how to best source animals for their translocation programmes. The inclusion of historical samples, where possible, strengthens monitoring by allowing assessment of changes in genetic diversity over time and by providing a benchmark for future improvements in diversity via management practices. Here, we used reduced representation sequencing (ddRADseq) data to report on the current genetic health of three remnant and seven translocated boodie ( Bettongia lesueur ) populations, now extinct on the Australian mainland. In addition, we used exon capture data from seven historical mainland specimens and a subset of contemporary samples to compare pre‐decline and current diversity. Both data sets showed the significant impact of population founder source (whether multiple or single) on the genetic diversity of translocated populations. Populations founded by animals from multiple sources showed significantly higher genetic diversity than the natural remnant and single‐source translocation populations, and we show that by mixing the most divergent populations, exon capture heterozygosity was restored to levels close to that observed in pre‐decline mainland samples. Relatedness estimates were surprisingly low across all contemporary populations and there was limited evidence of inbreeding. Our results show that a strategy of genetic mixing has led to successful conservation outcomes for the species in terms of increasing genetic diversity and provides strong rationale for mixing as a management strategy.

Per- and polyfluoroalkyl substances (PFAS) in the rivers of the Western United States - D. B. Sims; J. R. Monk; D. Woldetsadik; A. C. Hudson; M. C. Garner; K. Lindley; J. Piacentini; A. C. Buch; C. Cohu; C. S. Duvall; J. Blaszczak; J. Krause; et al. (International Journal of Environmental Science and Technology, 2025)

A framework for optimising opportunistic collaborative syntheses to propel ecological conservation - Ana M.M. Sequeira; Amanda E. Bates; Graeme Hays; David W. Sims; Samantha Andrzejaczek; Asta Audzijonyte; Julia K. Baum; Martin Beal; Barbara Block; Joshua Cinner; Kaitlyn Cowley; Eric Gilman; et al. (Biological Conservation, 2024)

Validation of a laboratory craving assessment and evaluation of 4 different interventions on cravings among adults with overweight or obesity - Ellen K. Pasquale; David R. Strong; Dawn M. Eichen; Carol B. Peterson; D. Eastern Kang-Sim; Kerri N. Boutelle (Appetite, 2024)

Recurrent selection shapes the genomic landscape of differentiation between a pair of host‐specialized haplodiploids that diverged with gene flow - Ashleigh N. Glover; Vitor C. Sousa; Ryan D. Ridenbaugh; Sheina B. Sim; Scott M. Geib; Catherine R. Linnen (Molecular Ecology, 2024)
Understanding the genetics of adaptation and speciation is critical for a complete picture of how biodiversity is generated and maintained. Heterogeneous genomic differentiation between diverging taxa is commonly documented, with genomic regions of high differentiation interpreted as resulting from differential gene flow, linked selection and reduced recombination rates. Disentangling the roles of each of these non‐exclusive processes in shaping genome‐wide patterns of divergence is challenging but will enhance our knowledge of the repeatability of genomic landscapes across taxa. Here, we combine whole‐genome resequencing and genome feature data to investigate the processes shaping the genomic landscape of differentiation for a sister‐species pair of haplodiploid pine sawflies, Neodiprion lecontei and Neodiprion pinetum . We find genome‐wide correlations between genome features and summary statistics are consistent with pervasive linked selection, with patterns of diversity and divergence more consistently predicted by exon density and recombination rate than the neutral mutation rate (approximated by dS). We also find that both global and local patterns of F ST , d XY and π provide strong support for recurrent selection as the primary selective process shaping variation across pine sawfly genomes, with some contribution from balancing selection and lineage‐specific linked selection. Because inheritance patterns for haplodiploid genomes are analogous to those of sex chromosomes, we hypothesize that haplodiploids may be especially prone to recurrent selection, even if gene flow occurred throughout divergence. Overall, our study helps fill an important taxonomic gap in the genomic landscape literature and contributes to our understanding of the processes that shape genome‐wide patterns of genetic variation.

Occurrence, source, and ecological risk of pharmaceuticals and illicit drugs in surface water in Las Vegas, USA - D. B. Sims; J. R. Monk; M. C. Garner; A. C. Hudson; J. E. Keller; C. Aguaiza; K. Lindley; D. Woldetsadik; A. C. Buch (International Journal of Environmental Science and Technology, 2024)

Influence and characteristics of anticyclonic eddies in active MHW years in the Northwest Atlantic - Lydia D. Sims; Bulusu Subrahmanyam; Corinne B. Trott (Frontiers in Marine Science, 2023)
The Northwest Atlantic contains two subregions, the Gulf of Maine and the Mid-Atlantic Bight. This region is dynamically controlled by the Jet Stream, the Gulf Stream, (GS) and its eddies. Anticyclonic eddies (AEs) (warm core clockwise eddies) and cyclonic eddies (cold core counterclockwise eddies) influence oceanic properties as they are shed by the GS and dissipated in the Northwest Atlantic. Marine Heatwaves (MHWs) are extreme temperature events that cause ecological damage in the Northwest Atlantic where drivers for these events are abundant. This work focuses on four major MHW active years (2012, 2016, 2017, and 2020) and observes the characteristics of MHWs, AEs, and oceanic parameters, such as Ocean Heat Content, Mixed Layer Depth, temperature, and salinity anomalies. Depth profiles, lead-lag covariance and correlations, and comparisons of events reveal dynamics of MHW intensification in these four years. AE radius, amplitude, and eddy kinetic energy (EKE) were less variable in the MHW years of 2012, 2016, and 2017 but have a weak relationship with MHW intensity. The Gulf of Maine had the strongest (above 0.80) correlation between GS eddy heat flux convergence and MHW intensity. The 2012 MHWs were shown to be strongly influenced by the GS in addition to atmospheric forcings, as were the 2017 Gulf of Maine MHWs. The 2020 MHWs experienced a number of forcings from the Jet Stream, the GS, and AEs, with the highest intensity events occurring at depths below 100 m. We conclude that better understanding how regional dynamics and multiple drivers intensify MHWs to form MHW active years is key to modelling and forecasting future extreme events.

The dynamic influence of subsurface geological processes on the assembly and diversification of thermophilic microbial communities in continental hydrothermal systems - Kenneth W.W. Sims; Cole M. Messa; Sean R. Scott; Andrew D. Parsekian; Andrew Miller; Abraham L. Role; Timothy P. Moloney; Everett L. Shock; Jacob B. Lowenstern; R. Blaine McCleskey; Matthew A. Charette; Bradley J. Carr; et al. (Geochimica et Cosmochimica Acta, 2023)

Extinct groundwater discharge locality in the Eldorado Valley; eastern Mojave Desert, Nevada, USA - Douglas B. Sims; Amanda C. Hudson; John E. Keller; Paul McBurnett; David Ferrari; Giavanna M. Fernandez; Juan Garcia-Hernandez; Bailey D. Kesl; Flavio W. Rodriguez; Sean G. Torres (Journal of Sedimentary Environments, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Animal-Borne Telemetry: An Integral Component of the Ocean Observing Toolkit - Rob Harcourt; Ana M. M. Sequeira; Xuelei Zhang; Fabien Roquet; Kosei Komatsu; Michelle Heupel; Clive McMahon; Fred Whoriskey; Mark Meekan; Gemma Carroll; Stephanie Brodie; Colin Simpfendorfer; et al. (Frontiers in Marine Science, 2019)

Predicting the risk of cucurbit downy mildew in the eastern United States using an integrated aerobiological model - K. N. Neufeld; A. P. Keinath; B. K. Gugino; M. T. McGrath; E. J. Sikora; S. A. Miller; M. L. Ivey; D. B. Langston; B. Dutta; T. Keever; A. Sims; P. S. Ojiambo (International Journal of Biometeorology, 2018)

Investigating Climate Change Impacts and Thresholds: An Application of the CLIMPACTS Integrated Assessment Model for New Zealand Agriculture - G. J. Kenny; R. A. Warrick; B. D. Campbell; G. C. Sims; M. Camilleri; P. D. Jamieson; N. D. Mitchell; H. G. McPherson; M. J. Salinger (Climatic Change, 2000)

Mapping the bovine factor H gene to Chromosome 16 by SSCP analysis - J. L. Williams; D. H. Lester; V. M. Teres; W. Barendse; R. B. Sim; C. J. Soames (Mammalian Genome, 1997)